2017
DOI: 10.1186/s12876-017-0691-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive pancreaticoduodenectomy for periampullary disease: a comprehensive review of literature and meta-analysis of outcomes compared with open surgery

Abstract: BackgroundMinimally invasive pancreatoduodenectomy (MIPD) has been gradually attempted. However, whether MIPD is superior, equal or inferior to its conventional open pancreatoduodenectomy (OPD) is not clear.MethodsStudies published up to May 2017 were searched in PubMed, Embase, Cochrane Library, and Web of Science. Main outcomes were comprehensively reviewed and measured including conversion to open approach, operation time (OP), estimated blood loss (EBL), transfusion, length of hospital stay (LOS), overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 120 publications
0
48
0
2
Order By: Relevance
“…Moreover, LPD was significantly associated with decreased blood loss in the Indian study, whereas LPD was associated with a lower major morbidity rate in the Spanish study . The advantages of LPD over its open counterpart have also been reported in numerous retrospective case–control studies …”
Section: Discussionmentioning
confidence: 72%
“…Moreover, LPD was significantly associated with decreased blood loss in the Indian study, whereas LPD was associated with a lower major morbidity rate in the Spanish study . The advantages of LPD over its open counterpart have also been reported in numerous retrospective case–control studies …”
Section: Discussionmentioning
confidence: 72%
“…Stauffer et al, reported a median operative time of 518 min, which was signi cantly longer than that in open surgery (140 min) [27]. The learning curve can be overcome in high volume centers, with average LPD operative times decreasing to less than 400 min [33]. However, due to tumor biology and the aggressiveness of the disease process, LPD for PDAC treatments are not commonly performed making it di cult to overcome the associated learning curve [6].A recent study from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) demonstrated that longer operative times were independently associated with worse perioperative outcomes after pancreatic resections [34].…”
Section: Discussionmentioning
confidence: 99%
“…Stauffer et al, reported a median operative time of 518 min, which was signi cantly longer than that in open surgery (140 min) [22]. The learning curve can be overcome in high volume centers, with average TLPD operative times decreasing to less than 400 min [26]. However, due to tumor biology and the aggressiveness of the disease process, TLPD for PDAC treatments are not commonly performed making it di cult to overcome the associated learning curve [5].…”
Section: Discussionmentioning
confidence: 99%